2015
DOI: 10.1038/srep08997
|View full text |Cite
|
Sign up to set email alerts
|

PIK3R1 negatively regulates the epithelial-mesenchymal transition and stem-like phenotype of renal cancer cells through the AKT/GSK3β/CTNNB1 signaling pathway

Abstract: The phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) pathway has been identified as an important pathway in renal cell carcinoma (RCC). We have reported a nonsense mutation in PIK3R1, which encodes the regulatory subunit of PI3K, in a metastatic RCC (mRCC), while the mutation was absent in the corresponding primary RCC (pRCC). To identify the function of PIK3R1 in RCC, we examined its expression in normal kidney, pRCC and mRCC by immunohistochemistry and real-time polymerase chain reaction. The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 45 publications
(82 reference statements)
5
47
0
Order By: Relevance
“…In this RCC model the vast majority (122/160) of genes induced by hypoxia in wt-VHL transfected 786-O ( VHL + ) cells are not significantly up-regulated in VHL mutated 786-O cells, confirming that the loss of VHL is not equivalent to hypoxic exposure and that in RCC, the VHL tumor suppressor has a distinct role from its activity in the hypoxia-inducible pathway [57]. Interestingly, side populations (SPs) of higher tumorigenicity were observed in this cell line, proving its usefulness in cancer stem cell studies [58, 59]. Surface receptors also confirm the ccRCC phenotype of 786-O cells, as these cells are positive for CD10 [60] and vimentin [61].…”
Section: Introductionmentioning
confidence: 70%
“…In this RCC model the vast majority (122/160) of genes induced by hypoxia in wt-VHL transfected 786-O ( VHL + ) cells are not significantly up-regulated in VHL mutated 786-O cells, confirming that the loss of VHL is not equivalent to hypoxic exposure and that in RCC, the VHL tumor suppressor has a distinct role from its activity in the hypoxia-inducible pathway [57]. Interestingly, side populations (SPs) of higher tumorigenicity were observed in this cell line, proving its usefulness in cancer stem cell studies [58, 59]. Surface receptors also confirm the ccRCC phenotype of 786-O cells, as these cells are positive for CD10 [60] and vimentin [61].…”
Section: Introductionmentioning
confidence: 70%
“…Notch2+ human pancreatic cancer Bxpc-3 and Panc-1 cells have properties of CSCs, which have a strong tumourigenic ability (Zhou et al, 2013). Depletion of CTNNB1 impaired the stem-like phenotype of renal cell carcinoma (Lin et al, 2015). Indeed, the WNT/CTNNB1 signaling is involved in regulating many types of stem cells (He K. et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…CD133+ cells isolated from primary tumors (nephrectomy specimens) of RCC were shown to promote tumor vascularization and neoangiogenesis in the nude mice model [37]. In another trial, CD133+/CD24+/CTR2+ cells were tumorigenic and indicated as RCC CSCs/TICs [55], as well as CD44+/CD133+/CXCR4+ [49] and CD44+/CD105+/CD133+/CD90+ cells [56]. In our study, CD133 was expressed at low levels in established RCC cell lines, which is in accordance with previous data [38, 57].…”
Section: Discussionmentioning
confidence: 99%